Modelling the Transport Flows in Marijampolė (Lithuania) - Vytautas Grigonis; Gražvydas Mykolas Paliulis (The Baltic Journal of Road and Bridge Engineering)
Every town is a framework driven by local inhabitants’ needs, filled with the ideas of local planners and influenced by global and local economical conditions. Consequently, it is crucial to find economically reasonable and sustainable infrastructural solutions to many problems which include traffic flow. A comparison and substantiation of various urban transport infrastructure development strategies in small Lithuanian towns and a documentation of these strategies are an essential part of comprehensive urban plans. An analysis concentrating on the town Marijampolė, as a case study, ie modelling transport flows with software VISUM 9.3 and comparison of the infrastructure development strategies are presented in this article.